Comprehensive genomic analysis of dietary habits in UK Biobank identifies hundreds of genetic associations - Joanne B. Cole (Nature Portfolio, 2020)
The choice of food intake is at least partially influenced by genetics, even though the effect sizes appear rather modest. Here, Cole et al. perform GWAS for food intake (85 individual food items and 85 derived dietary patterns) and test potential causal relationships with cardiometabolic traits using Mendelian randomization.